Umbilical artery Doppler at 19 to 22 weeks of gestation in the prediction of adverse pregnancy outcomes. (16th April 2014) - De Paco, Catalina; Ventura, Walter; Oliva, Raquel; Miguel, Myriam; Arteaga, Alicia; Nieto, Anibal; Delgado, Juan L.; Ghidini, Alessandro; Gratacos, Eduard
ABSTRACT Objective The aim of this study was to determine the clinical utility of Doppler assessment of the umbilical artery in the second trimester scan for predicting adverse pregnancy outcomes. Methods Singleton pregnancies that had undergone routine anomaly scan at 19 to 22 weeks of gestation with umbilical and uterine artery Doppler measurements. Receiver operating characteristic curves were constructed to evaluate the ability of umbilical artery pulsatility index (PI) to predict small for gestational age and preeclampsia. Results The final study population comprised 4565 singleton pregnancies. Multiple regression analysis showed significant independent contribution of umbilical artery PI in predicting SGA <10th and SGA <5th centiles (adjusted odds ratios of 2.51 and 3.51, respectively). By using a cutoff of umbilical artery PI >90th centile, the likelihood ratio of SGA <5th centile is 2.3 (95% CI: 1.7–3.0). Conclusions Umbilical artery PI at 19 to 22 weeks of gestation is significantly associated with SGA below the tenth and fifth centiles. A multivariate model combining umbilical and uterine artery Doppler measurements with additional maternal and sonographic characteristics may help predict small for gestational age, particularly those below the fifth centile. © 2014 John Wiley & Sons, Ltd.